2011
DOI: 10.1016/j.otsr.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Is patella eversion during total knee arthroplasty crucial for gap adjustment and soft-tissue balancing?

Abstract: The flexion gap inclination obtained without patellar eversion was steeper than with patellar eversion. This induced more externally rotated femoral positioning in absence of patellar eversion. These results ought to be taken into account by surgeons considering switching from conventional to MIS-TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Similarly, the lack of an "anterior" tether effect may explain the drop in pressures seen at full flexion when compared to the loads of the lateral compartment observed with the patella in a physiologic condition. The latter two findings have been observed by other investigators utilizing cadaveric [4] and intraoperative [7,18] models. Yoshino et al evaluated a novel intraoperative load-measuring device for PS and CR TKAs in 50 knees with a preoperative varus mal-alignment.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Similarly, the lack of an "anterior" tether effect may explain the drop in pressures seen at full flexion when compared to the loads of the lateral compartment observed with the patella in a physiologic condition. The latter two findings have been observed by other investigators utilizing cadaveric [4] and intraoperative [7,18] models. Yoshino et al evaluated a novel intraoperative load-measuring device for PS and CR TKAs in 50 knees with a preoperative varus mal-alignment.…”
Section: Discussionsupporting
confidence: 80%
“…The patella is lateralized or everted in order to adequately visualize the lateral compartment and balance the flexion gap. It is conceivable that a dislocated patella and consequently lateralized extensor mechanism would act as a tether and consequently affect the compartment loads [4,5,7,11,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they concluded that the load www.intechopen.com in the flexion gap will increase in PS TKA or, in other words, the flexion gap distance will decrease by resetting [34]. With the use of an offset type tensor which has been developed based on our tensor, Kamei et al reported a joint gap size and inclination measured intraoperatively on a knee in 90° flexion, with and without patellar eversion [35]. In the condition after tibial and distal femoral cut, they showed that the joint gap with patella in situ (17.0±3.4 mm) was significantly greater than with patellar eversion (15.4±3.0 mm), as was gap inclination at 90° flexion with the patella in situ (4.9±3.1°) compared to with patellar eversion (4.0±2.9°).…”
Section: Soft Tissue Balance With Reduced Pf Jointmentioning
confidence: 98%
“…In a series of intraoperative soft tissue balance assessments, we emphasized the importance of maintaining a reduced and anatomically oriented PF joint in order to obtain accurate and more physiologically-relevant soft tissue balancing. Recent studies have emphasized the importance of the physiological post-operative knee condition in assessing soft tissue balance with PF joint reduction and femoral trial replacement in place [33][34][35]. Using our tensor with a 5-mm-long minute uniaxial foil strain gauge, Gejyo et al reported a similar kinematic pattern of intra-operative joint component gap; when the patella was reduced, the joint gap was decreased at 90 and 135 degrees of flexion (by 1.9 mm and 5.5 mm, respectively) compared with the gap with the patella everted.…”
Section: Soft Tissue Balance With Reduced Pf Jointmentioning
confidence: 99%